2008
DOI: 10.1086/589988
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Echoes Reveal the Shock Breakout of the Cas A Supernova

Abstract: Through the serendipitous discovery of infrared echoes around the Cas A supernova remnant, the Spitzer satellite has provided astronomers with a unique opportunity to study the properties of the echoing material and the history and nature of the outburst that generated these echoes. In retrospect, we find that the echoes are also clearly visible as infrared ''hot spots'' in IRAS images of the region. The spectra of the echoes are distinct from that of the dust in the general diffuse interstellar medium (ISM ),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 32 publications
(53 reference statements)
6
57
0
Order By: Relevance
“…The SN becomes visible when the shock breaks through the surface of the star. Shock breakout has been the subject of numerous analytical studies (Colgate 1974;Matzner & McKee 1999;Nakar & Sari 2010;Piro et al 2010;Katz et al 2012) and numerical studies (Ensman & Burrows 1992;Blinnikov et al 2000;Tominaga et al 2009;Tolstov 2010;Kasen et al 2011;Blinnikov & Tolstov 2011;Tolstov et al 2013) in the past thirty years but has not been observed until more recently (e.g., Soderberg et al 2008;Gezari et al 2008;Schawinski et al 2008;Dwek & Arendt 2008).…”
Section: Spectramentioning
confidence: 99%
“…The SN becomes visible when the shock breaks through the surface of the star. Shock breakout has been the subject of numerous analytical studies (Colgate 1974;Matzner & McKee 1999;Nakar & Sari 2010;Piro et al 2010;Katz et al 2012) and numerical studies (Ensman & Burrows 1992;Blinnikov et al 2000;Tominaga et al 2009;Tolstov 2010;Kasen et al 2011;Blinnikov & Tolstov 2011;Tolstov et al 2013) in the past thirty years but has not been observed until more recently (e.g., Soderberg et al 2008;Gezari et al 2008;Schawinski et al 2008;Dwek & Arendt 2008).…”
Section: Spectramentioning
confidence: 99%
“…The SEDs of such echoes tend to peak in the 20-100 μm region, allowing echo detection in nearby galaxies by Spitzer during its cold mission. Spitzerbased evidence of this phenomenon in the Milky Way Galaxy has been presented for the Cassiopeia A SN (Krause et al 2005;Kim et al 2008;Dwek & Arendt 2008). Meikle et al (2007) showed that an IS IR echo provided a natural explanation for the strength and decline of the 24 μm flux between 670-681 days and 1264 days in SN 2003gd in the SA(s)c galaxy NGC 628 (M74).…”
Section: An Interstellar Echomentioning
confidence: 99%
“…Their main scientific conclusion is that most if not all of these IR echoes are caused by a recent X-ray flare of the Cas A SNR based on their apparent motions. However, the analysis was flawed because it did not account for the fact that the apparent motion strongly depends on the inclination of the scattering dust filament (Dwek & Arendt 2008;Rest et al, in preparation). Figure 4 illustrates how different dust sheet inclinations produce different apparent LE motions.…”
Section: Apparent Motionmentioning
confidence: 99%
“…However, their main scientific conclusion that the cause of most if not all of these IR echoes was a series of recent X-ray outbursts from the compact object in the Cas A SNR turned out to be incorrect. They neglected to take into account the fact that the apparent motion depends strongly on the inclination of the scattering dust filament (Dwek & Arendt 2008; see also Section 3.3). Instead, the IR echoes are much more likely caused by the intense and short burst of EUV-UV radiation associated with the shock breakout of the Cas A SN itself (Dwek & Arendt 2008).…”
Section: Cas a Snmentioning
confidence: 99%
See 1 more Smart Citation